Analytical Hierarchy Process to Determine Drug Inventory at The Pharmaceutical Installation of UPT Puskesmas Mandala - Ritonga, Siti Juhroini; M. Fakhriza (Universitas Nusantara PGRI Kediri, 2025)
Inaccurate planning of drug needs can hamper health services, especially in facilities such as UPT Puskesmas Mandala. This research aims to help the process of determining drug supplies effectively by applying the Analytical Hierarchy Process (AHP) method. This method is used to determine priority weights based on four main criteria which include price, availability, popularity, and effectiveness. Data were obtained through observations and interviews at UPT Puskesmas Mandala, then analyzed using RapidMiner software. The results of the analysis show that Vitamin C drugs have the highest score of 0.327915 so they are the top priority in procurement, while Cetirizine is ranked lowest. This finding proves that the AHP method is able to prioritize objectively and systematically, so that it can be a solution in improving the efficiency of planning drug needs at puskesmas